Use of a Neonatal-Mouse Model to Characterize Vaccines and Strategies for Overcoming the High Susceptibility and Severity of Pertussis in Early Life - Martin Aispuro, Pablo; Ambrosis, Nicolás; Zurita, María Eugenia; Gaillard, María Emilia; Bottero, Daniela; Hozbor, Daniela Flavia (Frontiers in Microbiology, 2020)
Newborns and unvaccinated infants, compared to other age groups, are more susceptible to pertussis infection, manifesting severe symptoms leading to a higher mortality. The recent increase in pertussis cases demands more effective strategies to overcome this major health problem. In parallel with maternal-immunization, neonatal-immunization (NI) is a strategy needing revision. Here, using the intranasal-challenge-mouse-model we evaluated the protective capacity of NI in both naïve-mice and those with maternally acquired immunity. We tested our acellular-vaccine-candidate based on outer-membrane-vesicles derived from Bordetella pertussis (OMVP) that induces Th2-profile but also the recommended Th-profile for protection: Th1/Th17-profile and CD4 T-memory-cells that reside in the lungs. Commercial acellular-vaccine (aP) and whole cell-vaccine (wP) inducing mainly Th2-profile and Th1-profile, respectively, were also tested. Analyzing the induced immunity and protection capability of NI included in 1- or 2-dose schedules with the same or different types of vaccine, we detected that the aP-vaccine administered in either single- or 2-dose schedules protected against sublethal B. pertussis infection. Schedules consisting of doses of aP neonatally and of OMVP or wP vaccine during infancy greatly reduced bacterial lung colonization while inducing the highest levels of high-avidity anti-pertussis toxin(PTx) IgG. That OMVP or wP neonatal dose did not interfere with the protection of transferred maternal immunity was especially encouraging. Moreover, OMVP- or wP used as a neonatal dose enhanced the quality of the humoral immune response in immunized pups. Antibodies generated by OMVP-or wP-vaccinated mice born to aP-immunized mothers were of higher avidity than those from mice that harbored only maternal immunity; but when mothers and neonates were immunized with the same aP-vaccine, the humoral response in the neonates was partially suppressed through the blunting of the level of anti-PTx IgG induced by the neonatal aP dose. These results demonstrated that neonatal immunization is a possible strategy to be considered to improve the current pertussis epidemiology. For neonates without maternal-immunity, mixed-vaccination schedules that include the aP- and OMVP-vaccines appear to be the most appropriate to induce protection in the pups. For offspring from immune mothers, to avoid blunting-effect, NI should be carried out with vaccines other than those applied during pregnancy.